Examen especial a la cuenta del efectivo y equivalente al efectivo de la empresa comercial Multisa centro de acopio y distribución sociedad civil del cantón Latacunga de la provincia de Cotopaxi con corte del segundo semestre del 2021. - Cadena Guanoluisa, Gimmy Alexander (2023)
Given the demands of a globalized economy, commercial company must meet the requirements of the control bodies. Therefore, the aim of this integrated project is to analyze the cash component and its equivalents through an special financial audit examination, in order to verify the reasonableness of the financial statements of the commercial company Multisa collection and distribution center civil society of the Latacunga Canton of the Cotopaxi province with a cut-off date of the second semester of 2021, with the support of the theoretical framework it was possible to outline the importance of the variables of our study, a qualitative and quantitative research approach was applied, the first was use for the analysis of the characteristic provide by the primary sources of financial information regarding to cash; the second allowed the collection of information from the company through interviews and questionnaires applied to the financial department in charge of the audited accounts. In the process of the special examination, the financial audit phases were carried out: planning, execution and communication of results; in planning, a global knowledge of the company`s activities was obtained and a low risk assessment of 22% and high confidence assessment of 78%; the execution of the examination allowed us to calculate both the reasonableness of the balances of the Cash account through the analysis of the subaccounts, and the Banks account with the study of the detail subaccounts, which permitted us to identify sufficient and competent audit findings to reinforce our opinion. The financial statements presented are reasonable in all material respects and in accordance with the legal framework of the Ecuadorian Accounting Standards (NEC), reflecting the economic situation of Multisa CAD.